Computer Programming Learning - Piteira, Martinha (2018)
Piteira, M., Costa, C. J., & Aparicio, M. (2018). Computer Programming Learning: How to Apply Gamification on Online Courses? Journal of Information Systems Engineering & Management, 3(2), [11]. DOI: 10.20897/jisem.201811